Infant and young child feeding practices associated with nutritional status among children attending child welfare clinic in Kericho County, Kenya - Cheruiyot DK; Kamau D; Kahanya WK (Ibom Medical Journal)
Background: Breastfeeding is widely recognized as the gold standard for infant feeding in the first six months of life, providing essential nutrients and antibodies for optimal growth and development. However, suboptimal breastfeeding practices and inadequate complementary feeding can contribute to malnutrition. This study assessed complementary feeding practices associated with nutritional status in breastfed children.